Effect of aqueous herbal extracts on growth, plasma metabolites and meat characteristics of broiler - Camy, MLY; Redoy, MRA; Shuvo, AAS; Ray, BC; Rahman, MA; Al-Mamun, M (Bangladesh Journal of Animal Science, 2020)
The experiment was carried out for 4 weeks to find out the efficacy of herbal extracts supplementation in drinking water on production performance, plasma metabolites, carcass characteristics, and fat deposition of commercial broilers. A total of 200 straight run day-old chicks (Cobb-500) were divided into five treatment groups; T0=Basal diet, T1= Basal diet+10 ppm neem leaves extract, T2= Basal diet+10 ppm garlic leaves extract, T3= Basal diet+10 ppm plantain leaves extract, T4= Basal diet+10 ppm antibiotic growth promoter (AGP) each with four replications having 10 birds per replicate. All the herbal extracts and AGP were supplemented in drinking water. Ration in the form of crumble was offered to the birds ad libitum having ME=3060 kcal/kg and CP=22.5%. Body weight and feed intake were recorded weekly to calculate body weight gain (BWG) and feed conversion ratio (FCR). A total of 15 birds three from each treatment were sacrificed at the end of feeding trial and dressing parameters were evaluated. Sensory properties of broiler meat were assessed by a panel of experts. Feed intake, BWG and FCR varied (p<0.05) in all treated groups, and the higher BWG and improved FCR were found in AGP group. Triglyceride and very low-density lipoprotein content were lower (p<0.05) in all herbal treated groups than the control and elevated at AGP group. However, increased (p<0.001) dressing percentage and abdominal fat deposition were found in AGP group compared to herbal treated groups and the least value was found in plantain group which also exhibited lower (p<0.001) meat ether extract. Flavor (p=0.001), juiciness (p=0.002), tenderness (p=0.005) and overall acceptability (p<0.001) of broiler meat were significantly higher in herbal group over control and AGP group. The aqueous herbal extract supplementation could be an alternative to antibiotic growth promoter to enhance growth performance, plasma lipid profiles as well as to reduce abdominal fat and meat of either extract. Bang. J. Anim. Sci. 2019. 48 (2): 108-115